Prevalence, Risk Factors and Intervention for Depression and Anxiety in Pulmonary Hypertension: A Systematic Review and Meta-analysis - Mai, Aaron Shengting; Lim, Oliver Zi Hern; Ho, Yeung Jek; Kong, Gwyneth; Lim, Grace En Hui; Ng, Cheng Han; Ho, Cyrus; Ho, Roger; Lim, Yinghao; Kuntjoro, Ivandito; Tay, Edgar; Yip, James; et al. (Frontiers in Medicine, 2022)
Background: Current guidelines recommend psychological support for patients with pulmonary hypertension suffering from psychological adversity. However, little is known about the prevalence and risk factors of depression and anxiety in patients with pulmonary hypertension (PH). Methods: Medline and Embase were searched from inception to 6 May 2021. Meta-analysis of proportions using the generalized linear mixed model was conducted to analyze the pooled prevalence rates of depression and anxiety in PH patients. Risk factors for depression and anxiety in PH patients were evaluated using meta regression. Results: A total of 24 studies involving 2,161 PH patients were included. The pooled prevalence of depression in PH was 28.0% (95% CI: 20.5-36.8) and pooled prevalence of anxiety was 37.1% (95% CI: 28.7-46.4). There was a significantly higher prevalence of anxiety (p=0.0013) amongst PH patients in Asia (61.1%) compared to Europe (40.3%) and North America (22.9%). In terms of risk factors, congenital heart disease-related pulmonary arterial hypertension (PAH-CHD) were significantly associated with both depression (OR: 1.68, 95% CI: 1.27-2.23, p=0.024) and anxiety (OR: 1.63, 95% CI: 1.45-1.83, p=0.002). On the other hand, chronic thromboembolic pulmonary hypertension (CTEPH, OR: 1.18, 95% CI: 1.10-1.26, p=0.004) was significantly associated with depression, whereas worse pulmonary vascular resistance (β: 0.30, 95% CI: 0.09-0.52, p=0.005) and cardiac index (β: -0.96, 95% CI:-1.58 to -0.35, p=0.002) were significantly correlated with anxiety. Conclusion: The prevalence of anxiety and depression in PH patients is alarmingly high, with an increased prevalence of anxiety in Asia compared to Europe or North America. Psychological support is warranted for patients with PH, particularly those with underlying congenital heart disease, CTEPH, and severe disease.